Early Mobilization Post–Hip Fracture Surgery. (8th March 2019) - Kenyon-Smith, Timothy; Nguyen, Eric; Oberai, Tarandeep; Jarsma, Ruurd
Introduction: Early mobilization after hip fracture surgery is a widely practiced component of postoperative care. However, there is little evidence to suggest that early mobilization post–hip fracture surgery is beneficial in reducing postoperative complications. This study aims to investigate the effect of early mobilization following hip fracture surgery on postoperative complications. Materials and Methods: This study retrospectively included 240 patients (female = 165, male = 75, mean age: 82.2 years) admitted to a level 1 trauma center in Adelaide, Australia, for hip fracture surgery. The effect of early mobilization on postoperative complications was assessed along with premorbid status. Subgroup analysis of patients stratified by premorbid health was subsequently analyzed to reduce confounding. Results: The odds of developing a complication were 1.9 times higher if the patient remained bedbound compared to mobilizing. Early mobilization was favorable to delayed mobilization. On average, complication-free patients mobilized earlier (mean [M] = 29 hours) compared to patients who experienced complications (M = 38 hours). In particular, rates of delirium was significantly reduced in patients who mobilized compared to remaining bedbound. However, premorbid status varied greatly. Early mobilizers had significantly better premorbid health than patients who remained bedbound. Overall subgroup analysis of patients with similar premorbid health showed mobilization was not associated with a reduction in complications. With an exception of patients with poor premorbid health, who experienced a reduction in complications following early mobilization. Discussion: In general, early mobilization was associated with the same complication rates as delayed mobilization and remaining bedbound. Patients with poor premorbid health benefited most from early mobilization with reduced complication rates. Conclusion: Postoperative delirium and premorbid health were better indicators of postoperative outcomes than time to mobilization.